Peptide prodrugs for the treatment of CNS disorders: A perspective for new drugs - Chin, Chung Man [UNESP]; Chiba, Diego Eidy [UNESP]; Machado, Marcella Gabrielle Mendes [UNESP]; De Oliveira Vizioli, Ednir [UNESP]; Dos Santos, Jean Leandro [UNESP] (Bentham Science Publishers, 2014)
The treatment of central nervous system (CNS) diseases is a major challenge. The presence of the barrier intended to protect the brain from unwanted molecules also impairs the efficacy of CNS-targeted drugs. The discovery of drug targets for CNS diseases opens a door for the selective treatment of these diseases. However, the physicochemical properties of drugs, including their hydrophilic properties and their peripheral metabolism, as well as the blood-brain barrier, can adversely affect the therapeutic potential of CNS-targeted drugs. Although peptides are often metabolized by enzymes, they are of particular interest for the treatment of CNS diseases or as carriers to deliver drugs to the brain. In this review, we discuss the use of peptides as potential prodrugs for the treatment of CNS diseases. © 2014 Bentham Science Publishers.
Keywords: Blood-brain barrier; Central nervous system; Hydrophilic; Peptides; Peripheral metabolism; Physicochemical properties